2020
DOI: 10.1016/j.artd.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Portable Pneumatic Compression Device as Part of a Multimodal Aspirin-Based Approach in Prevention of Venous Thromboembolism in Outpatient Total Knee Arthroplasty

Abstract: Background: The purpose of this study is to review the incidence of symptomatic venous thromboembolism (VTE) in patients undergoing outpatient primary total knee arthroplasty (TKA) who used a portable pneumatic compression device as part of their VTE prophylaxis protocol. Methods: A retrospective review of all outpatient primary TKA procedures in which patients used ambulatory pneumatic compression pumps as part of their multimodal VTE prophylaxis was performed from 2016 through 2018. This yielded a cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…10, 12,31,32 Previous studies have shown that the combined use of mobile IPCDs and ASA is effective in reducing VTE incidence in patients undergoing TKA. 21,22 Crawford et al reviewed VTE rates in a retrospective cohort of 1,131 TKA patients at standard and high risk for VTE on a combined protocol of mobile IPCDs with either 81-mg ASA BID, 325-mg ASA BID, or stronger chemoprophylactic agents. 22 They found that their study's VTE events were in high-risk patients using non-ASA therapy and concluded that the combined protocol was effective for VTE prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10, 12,31,32 Previous studies have shown that the combined use of mobile IPCDs and ASA is effective in reducing VTE incidence in patients undergoing TKA. 21,22 Crawford et al reviewed VTE rates in a retrospective cohort of 1,131 TKA patients at standard and high risk for VTE on a combined protocol of mobile IPCDs with either 81-mg ASA BID, 325-mg ASA BID, or stronger chemoprophylactic agents. 22 They found that their study's VTE events were in high-risk patients using non-ASA therapy and concluded that the combined protocol was effective for VTE prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Crawford et al reviewed VTE rates in a retrospective cohort of 1,131 TKA patients at standard and high risk for VTE on a combined protocol of mobile IPCDs with either 81-mg ASA BID, 325-mg ASA BID, or stronger chemoprophylactic agents. 22 They found that their study's VTE events were in high-risk patients using non-ASA therapy and concluded that the combined protocol was effective for VTE prophylaxis. However, the authors did not attempt to compare or comment on the efficacy of VTE prevention in patients using a protocol without mobile IPCDs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations